2021
DOI: 10.3389/fnsys.2021.642349
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Pain Alters Functional Connectivity Between Anterior Cingulate Cortex and Hippocampus in Both Humans and a Rat Model

Abstract: The anterior cingulate cortex (ACC) and hippocampus (HIPP) are two key brain regions associated with pain and pain-related affective processing. However, whether and how pelvic pain alters the neural activity and connectivity of the ACC and HIPP under baseline and during social pain, and the underlying cellular and molecular mechanisms, remain unclear. Using functional magnetic resonance imaging (fMRI) combined with electrophysiology and biochemistry, we show that pelvic pain, particularly, primary dysmenorrhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 90 publications
(131 reference statements)
0
5
0
Order By: Relevance
“…Functional magnetic resonance imaging (fMRI) technology provides a new dimension in pain assessment [ 47 ]. fMRI has been used in clinical trials and animal studies related to pain [ 48 , 49 ]. These limitations should be considered in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Functional magnetic resonance imaging (fMRI) technology provides a new dimension in pain assessment [ 47 ]. fMRI has been used in clinical trials and animal studies related to pain [ 48 , 49 ]. These limitations should be considered in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Depression is not uncommon in DR patients and it has a negative impact on their condition. However, in recent years, an increasing amount of evidence from electrophysiology[ 43 ], functional imaging[ 44 ], and behavioral studies[ 45 ] have shown that the ACC is closely related to the management of pain. The ACC can be activated by nociceptive and contextual stimuli, and it can participate in pain management, especially affective pain.…”
Section: Discussionmentioning
confidence: 99%
“…Fornix forms efferent projection fibers of the hippocampus and also comprises commissural fibers connecting the hippocampus of both sides (5,10,(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Fornixmentioning
confidence: 99%